Hair Growth Stimulation Effect of Centipeda minima Extract: Identification of Active Compounds and Anagen-Activating Signaling Pathways - Byoung Ha Kim; Myong Jin Lee; Won-Yung Lee; Jaesung Pyo; Myoung-Sook Shin; Gwi Seo Hwang; Dongchul Shin; Chang Eop Kim; Eun-Seok Park; Ki Sung Kang (Biomolecules, 2021)
Centipeda minima (L.) A. Braun & Asch is a well-studied plant in Chinese medicine that is used for the treatment of several diseases. A recent study has revealed the effects of extract of Cetipeda minima (CMX) standardized by brevilin A in inducing hair growth. However, the mechanism of action of CMX in human hair follicle dermal papilla cells (HFDPCs) has not yet been identified. We aimed to investigate the molecular basis underlying the effect of CMX on hair growth in HFDPCs. CMX induced the proliferation of HFDPCs, and the transcript-level expression of Wnt family member 5a (Wnt5a), frizzled receptor (FZDR), and vascular endothelial growth factor (VEGF) was upregulated. These results correlated with an increase in the expression of growth-related factors, such as VEGF and IGF-1. Immunoblotting and immunocytochemistry further revealed that the phosphorylation of ERK and JNK was enhanced by CMX in HFDPCs, and β-catenin accumulated significantly in a dose-dependent manner. Therefore, CMX substantially induced the expression of Wnt signaling-related proteins, such as GSK phosphorylation and β-catenin. This study supports the hypothesis that CMX promotes hair growth and secretion of growth factors via the Wnt/β-catenin, ERK, and JNK signaling pathways. In addition, computational predictions of drug-likeness, together with ADME property predictions, revealed the satisfactory bioavailability score of CMX compounds, exhibiting high gastrointestinal absorption. We suggest that CMX could be used as a promising treatment for hair regeneration and minimization of hair loss.